Adolescents’ academic achievement and meaning in life: the role of self-concept clarity - Liu, Fang; Li, Hanqi; Sun, Haoyang; Wang, Peng; Qin, Mengyuan (Frontiers in Psychology, 2025)
Sense of meaning in life is closely related to adolescents’ well-being. While prior research has largely examined the effects of individual traits and environmental influences, adolescents’ personal experiences (e.g., academic achievement) also play a crucial role. This study investigates the relationship between adolescents’ academic achievement and their sense of meaning in life, with a focus on the moderating role of self-concept clarity. Drawing on the meaning-making model, we hypothesized that academic achievement would positively predict both the presence of and search for meaning in life, and that self-concept clarity would moderate these relationships. A total of 1,321 junior high school students (50.9% female; Mage = 12.39, SDage = 0.52) from Henan Province, China, participated in the study. Participants completed a self-report measure of academic achievement, along with standardized scales assessing meaning in life and self-concept clarity. Results indicated that academic achievement was positively correlated with both presence of meaning and search for meaning. Self-concept clarity moderated the relationship between academic achievement and meaning in life, adolescents with higher self-concept clarity and higher academic achievement reported greater presence of meaning and search for meaning. The findings demonstrate that academic achievement significantly contributes to adolescents’ sense of meaning in life, and critically, self-concept clarity acts as a moderating variable that amplifies this positive association. Interventions targeting self-concept development could be a promising avenue for enhancing adolescents’ meaning in life and overall well-being.